2008
DOI: 10.1103/physrevb.77.235119
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous structure and carrier tuning of dimorphic clathrateBa8Ga16Sn30

Abstract: We report structural, transport, and thermal properties of carrier-tuned Ba 8 Ga 16 Sn 30 single crystals with the type-1 clathrate structure ͑␤ phase͒, demonstrating that Ba 8 Ga 16 Sn 30 is a unique thermoelectric clathrate material wherein both the structure type and the carrier type are tunable. The results are compared with the properties of the better known type-8 structure ͑␣ phase͒ and of A 8 Ga 16 Ge 30 ͑A =Sr,Eu͒. Differential thermal analysis and powder x-ray diffraction show that both phases are st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
196
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(217 citation statements)
references
References 41 publications
20
196
0
1
Order By: Relevance
“…17,18) Suekuni et al prepared p-and n-type type-I Ba 8 Ga 16 Sn 30 (BGS-I) and BGS-VIII, and studied the thermoelectric properties. 19) Koga et al calculated the band structure and density of states for BGS-VIII with different Ga content and found repulsive GaGa force between the nearest neighbor position. 20) This feature has been confirmed in type-I clathrates theoretically and experimentally.…”
Section: )mentioning
confidence: 99%
“…17,18) Suekuni et al prepared p-and n-type type-I Ba 8 Ga 16 Sn 30 (BGS-I) and BGS-VIII, and studied the thermoelectric properties. 19) Koga et al calculated the band structure and density of states for BGS-VIII with different Ga content and found repulsive GaGa force between the nearest neighbor position. 20) This feature has been confirmed in type-I clathrates theoretically and experimentally.…”
Section: )mentioning
confidence: 99%
“…For type-I Ba 8 Ga 16 Sn 30 , the pure elements were mixed together based on the nominal composition followed by an initial arc melting in argon environment. Annealing in an evacuated quartz tube at 900 o C for 50 hours was then applied, followed by a controlled slow cooling to 500 o C in 80 hours 23,24 . X-ray diffraction (XRD) measurements were performed on a Bruker D8 X-ray Powder Diffractometer, and wavelength dispersion spectroscopy (WDS) measurements were done in a Cameca SX50 spectrometer.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The clathrate samples were prepared using the self-flux method, following a technique reported previously 23 . Because of the existence of a type-l/type-VIII dimorphism in Ba 8 Ga 16 Sn 30 , a carefully controlled annealing process is needed during the sample making procedure.…”
Section: Sample Preparationmentioning
confidence: 99%
“…1(b)), while β-BGS is a cubic (Pm − 3n, No.223) consists of six tetrakaidecahedra X 24 and two X 20 ( Fig.1(d)). It is reported that the guest Ba ions in α-BGS are on-center for the 8c-site in the X 20 cage and exhibit on-center harmonic-like vibrations, 8) whereas those in β-BGS are rotating among the off-center positions in the tetrakaidecahedron. 8) Especially, type I Ba 8 Si 46 shows superconductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] These compounds have the unique caged crystal structure where a "guest" ion enclosed in an over-sized cage can vibrate within an anharmonic potential, so called "rattling". Theoretically, the interaction between the rattling and conduction electrons are regarded as a multi-channel Kondo effect and gives rise to the heavy fermion behavior.…”
Section: Introductionmentioning
confidence: 99%